Application of Gamification Teaching in Disaster Education: Scoping Review - Shiyi Bai; Huijuan Zeng; Qianmei Zhong; Yuqi Shen; Lulu Cao; Mei He (JMIR Serious Games)
Abstract BackgroundWith climate change, the number of natural disasters is increasing globally, and the resulting weather-related events lead to increased loss of life and property. Meanwhile, the significance of disaster education is becoming increasingly important. Despite natural disasters being hard to predict, people’s responses to such events can be improved by education and training. Gamification, an innovative teaching method, has demonstrated great potential across various fields, including disaster education. ObjectiveWe aimed to investigate the different application types of gamification in disaster education, focusing on nursing staff, medical professionals, university students, and disaster relief workers. Specifically, the goal was to identify the types of gamified teaching used in disaster education. MethodsThis scoping review was conducted according to the Joanna Briggs Institute methodology. The Participants, Concept, Context (PCC) model was used to frame the inclusion criteria. We performed a systematic search of the relevant literature across the Cochrane Library, PubMed, CINAHL, Embase, Web of Science, CNKI, Wanfang, VIPC, and SinoMed databases. Articles published in Chinese and English were selected for the review. The search was conducted to identify literature published from the establishment of the respective databases to April 21, 2024. Two researchers independently screened the literature according to the inclusion and exclusion criteria and extracted the data. ResultsWe included a total of 16 studies in this review, originating from 8 different countries. These studies involved 1744 participants: nursing students (n=451), medical students from other majors (n=420), college students (n=287), hospital decision makers (n=264), hospital medical staff (n=262), and disaster relief workers (n=60). The gamification approaches for teaching and learning encompassed the following 7 categories: tabletop games, serious games, scenario simulation games, virtual reality and mobile games, theme games, board games, and escape room games. The objectives of the studies were diverse. Three studies conducted randomized controlled trials, with only 1 performing a comparative analysis between different games. Two studies carried out long-term outcome evaluations. ConclusionsThis scoping review explored 7 types of games for disaster education and provided evidence for future education and training. Further research is needed to establish a long-term evaluation mechanism and a better game-based teaching program to provide more insights into the future of disaster education.